Thermofluid design and analysis of centrifugal compressors for a 50 MWe concentrated solar power supercritical CO₂ Brayton power cycle - De Villiers, Caroline Michelle (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.